The association between physical activity and mental health during the first year of the COVID-19 pandemic: a systematic review - Marconcin, Priscila (2022)
Introduction: The Coronavirus disease-19 (COVID-19) pandemic afected countries worldwide and has changed peoples’ lives. A reduction in physical activity and increased mental health problems were observed, mainly in the frst year of the COVID-19 pandemic. Thus, this systematic review aims to examine the association between physical activ ity and mental health during the frst year of the COVID-19 pandemic. Methods: In July 2021, a search was applied to PubMed, Scopus, and Web of Science. Eligibility criteria included cross-sectional, prospective, and longitudinal study designs and studies published in English; outcomes included physical activity and mental health (e.g., depressive symptoms, anxiety, positive and negative efects, well-being). Results: Thirty-one studies were included in this review. Overall, the studies suggested that higher physical activity is associated with higher well-being, quality of life as well as lower depressive symptoms, anxiety, and stress, indepen dently of age. There was no consensus for the optimal physical activity level for mitigating negative mental symp toms, neither for the frequency nor for the type of physical activity. Women were more vulnerable to mental health changes and men were more susceptive to physical activity changes. Conclusion: Physical activity has been a good and efective choice to mitigate the negative efects of the COVID-19 pandemic on mental health during the frst year of the COVID-19 pandemic. Public health policies should alert for possibilities to increase physical activity during the stay-at-home order in many countries worldwide.